Teachers' understandings of shyness: Psychosocial differentiation for student inclusion. (19th July 2019) - Mjelve, Liv H.; Nyborg, Geir; Edwards, Anne; Crozier, W. Ray
Abstract : Shyness is not a recognised special educational need, yet studies reveal that shy children underperform academically and present psychosocial vulnerabilities. We present a Norwegian study of elementary school teachers who have experience in working with shy children. Framed by a cultural–historical understanding that concepts are tools employed by teachers as they work on problems of practice, the study examined (i) how shyness is a concept allowing teachers to interpret behaviours of children and (ii) why they employ the concept and what demands were being addressed. Data were gathered through post‐observation stimulated recall interviews with 8 teachers and three focus group sessions with 11 teachers. Seeing shyness as a tool for identifying the demands made by children regarded as shy, revealed sets of child behaviours which required two distinct forms of differentiation: (i) augmenting cognitive support with psychosocial feedback to help the child overcome the behaviours impeding their engagement as active learners and (ii) making extra efforts when eliciting children's understandings in order to give formative feedback and support progress through pedagogic sequences. By identifying the behaviours underpinning broad descriptions of shyness, such as anxiety, the analyses show that teachers employ shyness as an overarching concept which reveals psychosocial demands that may not be entirely addressed by the repertoires of responses available to them.